Didaktika naravoslovja in tehnike na razredni stopnji - Fošnarič, Samo; Dolenc, Kosta (University of Maribor Press, 2025)
Didactics of Science and Technology in the Primary School. The textbook Didactics of Science and Technology in the Primary Education guides teachers from the introductory course Environmental Studies to the specialised subject Science and Technology. It clarifies national aims, learning standards and cross-curricular links, then offers a toolkit for practice: lesson-planning phases, operative objectives, and classroom organisation (frontal, group, pair, individual). A core chapter contrasts teaching approaches – from transmissive and constructivist models to contemporary inquiry-based learning, problem-based learning, flipped classroom and technology-enhanced instruction – illustrated with concrete, step-by-step activity cycles. Further sections cover assessment strategies, development of spatial and temporal concepts, safety and material requirements for school laboratories/workshops, plus integration of digital tools and sustainability themes. The textbook closes with a concise history of science-technology education in Slovenia and a guide to interpreting technical documentation, making it a comprehensive handbook for both pre-service and in-service primary teachers.